One Hundred Years of Quail Management in Arizona - David E. Brown (National Quail Symposium Proceedings, 2017)
Populations of Gambel’s (Callipepla gambelii), scaled (C. squamata), and Montezuma (Cyrtornyx montezumae) quail in Arizona have fluctuated greatly in the 100 years since statehood as have regulations governing their take. The greatest fluctuations in numbers have been annual, but there is some evidence for a long-term decline in the numbers of all species. Quail hunt success has declined significantly since 1962 according to both check station information (r2 1⁄4 0.27; P,0.0001) and hunt questionnaire data (r2 1⁄4 0.35; P,0.001). Past attempts to improve or stabilize quail populations through bag limit and season adjustments have failed to impact quail numbers. Research investigating the influence of harvest on quail numbers showed that subsequent year population sizes fluctuated independent of harvest and that hunting had little effect on population size. Thus, season lengths increased over the years with late winter hunting opportunities becoming increasingly popular after 1979. Studies comparing hunted and non-hunted areas have not been conducted since late season hunting was initiated, and are needed to convince the public that quail populations in areas closed to late season hunting remain similar to those in areas open to late season hunting. Habitat conditions have also changed, deteriorating generally but improving on certain federal lands. Quail management efforts to improve hunt success by providing rainwater catchments and other habitat manipulations have not been effective at increasing population size, and water developments for livestock have resulted in long-term range deterioration. Decreasing population sizes and quail hunt success during the last 50 years, if due to environmental changes, cannot be addressed by regulation changes.
Keywords: Arizona; Callipepla gambelii; C. squamata; common raven; Corvus corax; Cyrtonyx montezumae; Gambel' s quail; hunt history; hunt success; Montezuma quail; population trend; scaled quail